The boundary behavior of holomorphic functions - Min, Baili (ProQuest Dissertations & Theses, 2011)
In the theory of several complex variables, the Fatou type problems, the Lindelöf principle, and inner functions have been well studied for strongly pseudoconvex domains. In this thesis, we are going to study more generalized domains, those of finite type. In Chapter 2 we show that there is no Fatou's theorem for approach regions complex tangentially broader than admissible ones, in domains of finite type. In Chapter 3 discussing the Lindelöf principle, we provide some conditions which yield admissible convergence. In Chapter 4 we construct inner functions for a type of domains more general than strongly pseudoconvex ones. Discussion is carried out in [special characters omitted].